Pemanfaatan Artificial Intelligence Guna Menunjang Transformasi Digital Pendidikan Bagi MGMP Akuntansi dan Keuangan Lembaga - Kholifaturrohmah, Ramita; Mayasari, Viviana; Najmudin, Najmudin; Misni Mulasiwi, Cut (Abimanyu : Jornal of Community Engagement, 2026)
Social changes in the era of Artificial Intelligence (AI) necessitate that both students and teachers adapt to new technologies in the learning process. Teachers of the Subject Teacher Forum (MGMP) for Accounting and Institutional Finance in Banyumas Regency face challenges in integrating AI into accounting learning. The purpose of this Community Service Program is to enhance teachers’ knowledge of AI and their capability to implement it in teaching. The community partners involved are 57 teachers from 21 Vocational High Schools (SMK) in Banyumas Regency. The implementation methods include: (1) needs identification, (2) planning for socialization and training, (3) socialization and training, and (4) follow-up and evaluation. The training outcomes offer both theoretical benefits, in the form of increased understanding of AI, and practical benefits through hands-on experience in utilizing AI within the learning process. Keywords: Artificial Intelligence, learning process, MGMP Accounting and Institutional Finance